PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, GOVERNANCE TERHADAP FUTURE FIRM VALUE DAN FUTURE FIRM PERFORMANCE PADA PERUSAHAAN INDONESIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2021 - Kholisa Nur Hidayah; Dewita Puspawati; Widowati Dian Permatasari (ITB AAS Indonesia Surakarta, 2024)
This research aims to examine the influence of Environmental, Social, Governance Disclosure on company value and performance in the future. The population in this research are companies that have been listed on the Indonesia Stock Exchange (BEI) in the 2020-2021 period. This research uses a data collection method using a purposive sampling method, then the data is analyzed using a multiple linear regression method. The results of this study show that the Environmental Disclosure has a significant effect on the future firm value and future firm performance as proxied by Tobin's Q and Return on Assets. Meanwhile, the Social and Governance Disclosure variables show do not affect future firm value and future firm performance.